Investigation of antimicrobial activities of some herbs containing essential oils and their mouthwash formulations - Kulaksız, Büşra; Er, Sevda; Üstündağ Okur, Neslihan; Saltan İşcan, Gülçin (Turkish Pharmacists Association, 2018)
Objectives: The aim of this study was to prepare pharmaceutical formulations of mouthwashes and to examine the antimicrobial activities of essential oils obtained from plants used traditionally in Turkey for oral infections. Materials and Methods: Essential oils were obtained from herbal drugs using water distillation with Clevenger apparatus. The antimicrobial capacities of mouthwash formulations containing a mixture of essential oils with proportions of 4.5% and 9.0% were examined using disc diffusion and microbroth dilutions. Results: The inhibition zone diameters were determined to vary between 7 and 59 mm. The static and cidal activity was generally 50% and greater than 50% when pure essential oil samples were applied on microorganism specimens. Formulation F2, which contained a mixture of essential oils with proportions of 4.5%, showed 6.25% minimum bactericidal effect on Staphylococcus aureus ATCC 25923, and 3.125% the minimum inhibitory concentration and minimum bactericidal concentration on all other microorganisms. The antimicrobial effect of pure essential oil samples applied on microorganisms was lower than of mouthwashes formulations; the antimicrobial effect of F2, which contained a mixture of essential oils with proportions of 4.5% was higher than formulation F1, which contained a mixture of essential oils with proportions of 9%. Conclusion: The results obtained by these methods allow us to conclude that the essential oils and the prepared F1 and F2 mouthwash formulations exerted activity against microorganisms affecting the oral cavity. The F2 formulation also had significant antimicrobial activity on the tested microorganisms.

Amaç: Türkiye’de halk arasında yaygın olarak kullanılan bitkilerden elde edilen uçucu yağların antimikrobiyal etkilerini araştırmak ve bu etkilerden yola çıkarak ağız enfeksiyonlarında kullanılmak üzere gargara formülasyonu hazırlamaktır. Gereç ve Yöntemler: Uçucu yağlar, bitkilerden (Origanum vulgare L. ssp. hirtum, Rosmarinus officinalis L., Laurus nobilis L., Salvia fruticosa Mill.) su distilasyonu metodu ile Clevenger apareyi kullanılarak elde edilmiştir. Elde edilen uçucu yağlar ve %4.5 ve %9.0 oranlarında uçucu yağların karışımını içeren gargara formülasyonlarının antimikrobiyal aktiviteleri disk difüzyon metodu ve mikrobroth dilüsyon metodu ile araştırılmıştır. Bulgular: Bu çalışmada antimikrobiyal aktivite disk difüzyon metodu ve mikrobroth dilüsyon metoduyla değerlendirilmiştir. İnhibisyon zon çaplarının 7-59 mm arasında değişkenlik gösterdiği belirlenmiştir. Uçucu yağlar, mikroorganizmalar üzerine saf olarak uygulandığında statik ve sidal etkinliğin genellikle %50 ve %50’nin üzerinde olduğu gözlenmiştir. %4.5 oranında uçucu yağ karışımı içeren F2 formülasyonunun Staphylococcus aureus ATCC 25923 üzerindeki minimum bakterisidal etkisinin %6.25 olduğu ve diğer tüm mikroorganizmalar üzerinde minimum inhibitör konsantrasyon ve minimum bakterisidal konsantrasyonunun %3.125 olduğu bulunmuştur. Uçucu yağ örneklerinin mikroorganizmalar üzerine saf olarak uygulandığında gösterdikleri antimikrobiyal etkinin, gargara formülasyonlarına göre daha düşük olduğu; ayrıca %4.5 oranında uçucu yağ karışımı içeren F2 formülasyonunun, %9.0 oranında uçucu yağ karışımı içeren F1 formülasyonuna göre test edilen tüm mikroorganizmalar üzerine daha yüksek antimikrobiyal etkiye sahip olduğu bulunmuştur. Sonuç: Elde edilen sonuçlar uçucu yağların karışımı ile hazırlanan F1 ve F2 formülasyonlarının, test edilen mikroorganizmalara karşı antimikrobiyal etkiye sahip olduğunu ortaya koymuştur. Ayrıca çalışma sonucunda F2 formülasyonunun test edilen mikroorganizmalar üzerinde önemli oranda antimikrobiyal aktiviteye sahip olduğu rapor edilmiştir.
Uçucu yağ içeren bazı bitkilerin ve gargara formülasyonlarının antimikrobiyal aktivitelerinin araştırılması
WOS: 000450780900020
Keywords: Antimicrobial Activity; Laurus Nobilis L.; Origanum Vulgare L. Ssp Hirtum; Rosmarinus Officinalis L.; Salvia Fruticosa Mill; Antimikrobiyal Aktivite; Laurus Nobilis L.; Origanum Vulgare L. Ssp. Hirtum; Rosmarinus Officinalis L.; Salvia Fruticosa Mill